Pengaruh Insentif Dan Motivasi Terhadap Kinerja PNS di Badan Kepegawaian Daerah - Nanda Ayu Rachmawati; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This research aims to analyze the effect of incentives and motivation on government employees performance. This research uses the quantitative method. The sample in this research used 59 government employees of the regional civil service agency Kabupaten Sidoarjo. This research used statistical analysis consists of validity and reliability test, classical assumption test, and multiple linear tests. The data is running by SPSS software version 20. The result of this research are incentives has a positive effect on government employee performance, but it is not significant. The result also show that motivation positively and significant on government employees performance. Afterwards, the test result also prove that incentives and motivation simultaneously have a positive effect on the performance of government employees. In this case, may the regional civil service agency use incentives to increase motivation among the employee or regional civil service agency does further research on why incentives do not have a significant effect on government employee performance.